Two CONSTANS-LIKE genes jointly control flowering time in beet. Issue 1 (December 2018) - Dally, Nadine; Eckel, Maike; Batschauer, Alfred; Höft, Nadine; Jung, Christian
Abstract Breeding vegetative crops (e.g. beets, cabbage, forage grasses) is challenged by two conflicting aims. For field production, flowering must be avoided while flowering and seed set is necessary for breeding and seed production. The biennial species sugar beet makes shoot elongation ('bolting') followed by flowering after a long period of cold temperatures. Field production in northern geographical regions starts in spring. A thickened storage root is formed only during vegetative growth. It is expected that winter beets, which are sown before winter would have a much higher yield potential. However, field production was not possible so far due to bolting after winter. We propose a strategy to breed winter beets exploiting haplotype variation at two major bolting time loci, B andB2 . Both genes encode transcription factors controlling the expression of two orthologs of the Arabidopsis geneFLOWERING LOCUS T (FT ). We detected an epistatic interaction between both genes because F2 plants homozygous for twoB/B2 mutant alleles did not bolt even after vernalization. Fluorescence complementation studies revealed that both proteins form a heterodimerin vivo . In non-bolting plants, the bolting activatorBvFT2 was completely downregulated whereas the repressorBvFT1 was upregulated which suggests that both genes acquire aCONSTANS (CO ) like function in beet. Like CO, B and B2 proteins house CCT and BBX domains which, in contrast to CO are split between the two beet genes. We propose an alternative regulation ofFT orthologs in beet that can be exploited to breed winter beets.